Tunable laser applications - Duarte, F.J (Optical engineering (Marcel Dekker, Inc.), 1995)
This work details tunable laser applications of broad interest, historical significance and potential future value. Atomic and molecular spectroscopy, interferometry, lightening triggering, imaging, laser radar, lidar and gyroscopes are discussed. The work focuses on various sources of coherent radiation such as optical parametric oscillators, external cavity semiconductors lasers, and dye, gas, C02, ultrashort-pulse and free-electron lasers.